Optimal Design and Sizing of Integrated Centralized and Decentralized Energy Systems. (May 2017) - Liu, Wen Hui; Alwi, Sharifah Rafidah Wan; Hashim, Haslenda; Muis, Zarina A.; Klemeš, Jiri J.; Rozali, Nor Erniza M.; Lim, Jeng Shiun; Ho, Wai Shin
Abstract: Concerns over sustainability of fossil fuels, and increasing awareness for the environment have encouraged countries all over the world to shift from the heavy reliance on fossil fuel to renewable energy (RE) resources for electricity generation. Although implementation of RE has been on the rise, large-scale deployment of RE still remains a challenge, especially in terms of economic and technicality. This paper proposes the integration of the current energy system (centralised energy system, CEG running on mainly fossil fuels) with the new energy system (decentralised energy system, DEG). Numerical analysis is developed to solve and target the proposed multiple DEGs and CEG integrated system at its optimum design and sizing. Two existing numerical approaches in Power Pinch Analysis are applied, i.e. Power Pinch Analysis (PoPA) for a smaller scale decentralised energy systems while the net energy deficit will be satisfied in a centralised energy system via Electric System Cascade Analysis (ESCA). The designated combination of Power Pinch methodology in this study is based on an hourly scale operation of both systems. With case study of five (5) DEG(s), the analysis indicates that DEG 1 has 540 MWh for energy-related capacity and 70 MW for power-related capacity. DEG 2, 480 MWh and 70 MW, DEG 3, 480 MWh and 120 MW, DEG 4, 1, 000 MWh and 150 MW, and DEG 5, 100 MWh and 90 MW. The CEG power plants should have a total capacity of 48.3 MW with energy storage of 270.6 MWh and 45.1 MW.